The Effect Size of Public Acconting Firm (KAP), Audit Tenure, Audit Fees, and Tax Aggressiveness on Audit Quality in Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Emiya Putri Febrisia Br Ginting; Sauh Hwee Teng; Herlin Munthe; Darwin Lie (Sean Institute, 2026)
This study aims to analyze the relationship between firm size, auditor tenure, audit fees, and tax aggressiveness on audit quality in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using purposive sampling, with the criteria that the sample consists of manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period and possessing complete data on the independent variables for that period. Based on these criteria, 20 companies were identified with a 3-year observation period, resulting in a total of 60 data points for the study. The data analysis method employed was multiple linear regression. This study indicates that the size of the public accounting firm (KAP), audit tenure, audit fees, and tax aggressiveness simultaneously have a significant effect on audit quality. Partially, the size of the KAP, audit fees, and tax aggressiveness have a significant effect on audit quality, whereas audit tenure does not have a significant effect on audit quality.